Application of protege and SPARQL in the field of project knowledge management - Dong, Hai; Hussain, Farookh; Chang, Elizabeth (IEEE, 2007)
Protg is a set of open-source ontology design software developed in Stanford Medical Informatics. SPARQL (Protocol and RDF Query Language) is recommended by W3C, to represent the RDF (Resource Description Framework) graph a set of triples that consist of a subject, a predicate and an object as the basic expression of data stored in OWLbased knowledge base.In this paper, we propose an ontology-based project knowledge management methodology, by means of Protg and SPARQL, to solve the issues in project management activities. By introducing a set of new ontology notations, we present the conceptual model of our ontology to realize the function of knowledge management in project organizations. Following that, we realize the prototype in Protg and validate it by means of SPARQL. Finally we make comments on our project and plan our future work.